To assess the role fiberoptic bronchoscopy in the evaluation of hemoptysis - Songara, Ashwin; Mukherjee, Rohit; Shikha, Swapnil; Solanki, Awadesh P. S.; Joshi, Tanay; Patel, Deepika (International Journal of Research in Medical Sciences, 2017)
Background: To prospectively evaluate the efficiency of the fiberoptic bronchoscopy (FOB) examination in the evaluation of patients with hemoptysis. Methods: We prospectively reviewed 50 patients who underwent FOB for hemoptysis. There were 39 male and 11 female. The mean age was 46 years with a range from 21 to 83 years. The patients were divided between two groups on the basis of their chest roentograms (46% with normal and 54% with abnormal findings). Results: Hemoptysis in normal and abnormal chest roentograms was respectively attributed to bronchiectasis in 5 (21.7%) and 3 (11.1%) cases, bronchogenic carcinoma in 2 (8.6%) and 9 (33.3%) cases, bronchitis in 2 (8.6%) and 3 (11.1%) cases, tuberculosis in 2 (8.6%) and 5 (18.5%) cases, cryptogenic causes in 8 (34.7%) and 4 (14.8%) cases and pseudohemoptysis in 2 (8.6%) cases (bleeding from upper respiratory tract). Conclusions: Fob plays a pivotal role in the evaluation of hemoptysis. It was found that left upper lobe followed by right upper lobe was the site most consistent with the findings, with bronchogenic carcinoma being the most common non- infectious cause. Infectious etiology was the most common pathology behind hemoptysis and bronchiectasis was the most important risk factor.